The effect of increasing knowledge and motivation of nurses on completeness of soap documentation during handover at x hospital, bogor district - Duma Elida; Emiliana Tarigan; Sudibyo Supardi (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2023)
Nurses have an obligation to make documentation of the nursing care actions they do in the form of SOAP. The purpose of this study was to determine the effect of increasing knowledge and motivation of nurses on the completeness of SOAP documentation during handovers at Hospital X Bogor Regency with a quantitative pre-experimental one group pretest and posttest research design. The sample of this study amounted to 53 people according to the inclusion criteria. The intervention carried out was training on SOAP documentation. The data collection tool is a questionnaire. Data analysis using SPSS with Wilcoxon test and che square test. The result of this research is the description of the characteristics of nurses with the largest percentage aged >35 years 50.9%, D3 nursing education 84.9%, and working period >5 years 62.3%. a description of the knowledge level of 84.9%, good motivation of 86.8%, an overview of the completeness of SOAP documentation after training of 45.2%. The results of the analysis of differences in nurses' knowledge about SOAP documentation, P value of 0.000 means that there is a significant difference between the level of knowledge and the completeness of filling out SOAP documentation during handover before and after training. The results of the analysis of the effect of increasing knowledge on increasing the completeness of SOAP documentation. P value > 0.05, which means that there is no significant effect of increasing knowledge on the completeness of SOAP documentation during handover. Suggestions need to supervise and assist in filling the completeness of SOAP documentation continuously and evaluate the incompleteness of SOAP documentation.